Sesbania aculeata: new host plant record for piezodorus guildinii in Paraná, Brazil - Panizzi, Antônio R. (Pesquisa Agropecuaria Brasileira, 2014)
Sesbania aculeata (Leguminosae) is reported as a new host plant record for Piezodorus guildinii (Hemiptera: Pentatomidae) in the region of Londrina, north of Paraná state, Brazil. Nymphs did complete their development and adults reproduced when fed pods of S. aculeata. The stink bugs Nezara viridula and Thyanta perditor, although able to feed on pods of S. aculeata in the field, showed poor nymphal development when reared in the laboratory on S. aculeata pods.